The Only Way is Ethics: Obtaining Approvals for NHS Clinical Research Projects. Issue 3 (5th July 2019) - Hendrickson, Susan; McKeown-Keegan, Sadie; Wright, Thomas; Carpenter, David
Setting up and running a research project can be a daunting endeavour, especially for clinicians for whom there is a professional aspiration and expectation to publish in the scientific literature despite often lacking a formal research degree and allocated time for research activity. This article aims to give NHS clinicians a step-by-step guide to obtaining governance and ethics approval.